The Chemical Bond II 100 Years Old and Getting Stronger - Mingos, D. Michael P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Arne Haaland and Mats Tilset--Lewis and Kossel's Legacy: Structure and Bonding in Main-Group Compounds Paul L.A. Popelier--Quantum Chemical Topology M. Kohout--Electron Pairs in Position Space Sason Shaik, David Danovich, Benoit Braida, Wei Wu, and Philippe C. Hiberty--New Landscape of Electron-Pair Bonding: Covalent, Ionic, and Charge-Shift Bonds Bernard Silvi--The Relevance of the ELF Topological Approach to the Lewis, Kossel, and Langmuir Bond Model Andrés Falceto and Santiago Alvarez--Comparison of the Cr-Cr Quadruple and Quintuple Bonding Mechanisms.
Keywords: Inorganic chemistry; Chemistry, Physical and theoretical; Physical chemistry; Inorganic Chemistry; Theoretical Chemistry; Physical Chemistry